An Experimental Study of Plastic Waste as Fine Aggregate Substitute for Environmentally Friendly Concrete - Nura Diana, Anita Intan; Fansuri, Subaidillah; Fatoni, Akhmad Feri (Advances in Technology Innovation, 2021)
Decomposing plastics, including plastic bottles, is a very difficult process because it takes 50-100 years. Every year, the use of plastic bottles is increasing, but only few people are willing to treat plastic bottle waste. In this study, plastic bottle waste is used as a substitute of fine aggregate and shaped in such a way to have a sand-like gradation. The variations of graded plastic bottle waste are 0%, 5%, 10%, and 12%. The test objects for each variation consist of three specimens. Data are analyzed by using regression and classical assumption test with SPSS program. The results of the data analysis show that there is a simultaneous effect on the compressive strength with variations in plastic waste substitution. The compressive strength decreases with the increase in the percentage of plastic added. Maximum compressive strength is at the variations of 0% and 5% with19.192 MPa and 16.414 MPa, respectively.